2009
DOI: 10.4161/cc.8.4.7657
|View full text |Cite
|
Sign up to set email alerts
|

Paths of FGFR-driven tumorigenesis

Abstract: Fibroblast growth factor receptors (FGFRs) comprise a subfamily of receptor tyrosine kinases (RTKs) that are master regulators of a broad spectrum of cellular and developmental processes, including apoptosis, proliferation, migration and angiogenesis. Due to their broad impact, FGFRs and other RTKs are highly regulated and normally only basally active. Deregulation of FGFR signaling by activating mutations or ligand/receptor overexpression could allow these receptors to become constitutively active, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 116 publications
3
119
0
Order By: Relevance
“…Of note, in prostate cancer cell lines, the levels of FGF-2 and FGFR1 have been shown to increase proportionally to the degree of cancer aggressiveness and castration resistance (Nakamoto et al, 1992;Cronauer et al, 1997). The analysis of tumor specimens has shown that enhanced FGF signaling results in increased proliferation, invasiveness and resistance to therapy in several solid and hematological malignancies (Menzel et al, 1996;Konig et al, 1997;Song et al, 2000;Sezer et al, 2001;Acevedo et al, 2009;Turner et al, 2010). Moreover, hemi-or homozygous inactivation of Fgf-2 alleles in TRAMP mice with transgenic prostate adenocarcinoma resulted in increased survival by inhibiting progression toward a poorly differentiated and highly metastatic phenotype (Polnaszek et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in prostate cancer cell lines, the levels of FGF-2 and FGFR1 have been shown to increase proportionally to the degree of cancer aggressiveness and castration resistance (Nakamoto et al, 1992;Cronauer et al, 1997). The analysis of tumor specimens has shown that enhanced FGF signaling results in increased proliferation, invasiveness and resistance to therapy in several solid and hematological malignancies (Menzel et al, 1996;Konig et al, 1997;Song et al, 2000;Sezer et al, 2001;Acevedo et al, 2009;Turner et al, 2010). Moreover, hemi-or homozygous inactivation of Fgf-2 alleles in TRAMP mice with transgenic prostate adenocarcinoma resulted in increased survival by inhibiting progression toward a poorly differentiated and highly metastatic phenotype (Polnaszek et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Tie-2 and VEGFR-1/-2 are selectively expressed by endothelial cells, 106 and FGFs promote angiogenesis via dependent crosstalk between FGF-VEGF signaling axes. 107 The FGF signaling axis has been shown to be essential during EMT stages through regulation of the EMT-associated zinc finger transcription factor, Snail, a transcriptional repressor of the epithelial phenotype caretaker, E-cadherin. 108 VEGF-induced Src activation has also been implicated in the progression and metastasis of various solid tumors, but an alternative intrinsic mechanism of Src activation may be important in both cancer and stromal cells.…”
mentioning
confidence: 99%
“…Furthermore, FGF-2, IIIc ligand, was also overexpressed indicating its role along with that of IIIc isoform in the epithelial cell division. Hence, the conversion of non-invasive epithelial cells to the malignant phenotype [91] is due to the switch that ensures the FGFR2 signaling through the IIIc isoform (expressed by mesenchymal cells and hence has the potency to invade surrounding tissues) rather than the IIIb isoform. FGFR2-IIIb isoform has also been described to possess repressive tumor properties.…”
Section: Fgf and Fgfrs: Roles In Cancermentioning
confidence: 99%